Preparation method and application of pure-phase 2D perovskite passivation layer
The preparation of a pure phase 2D perovskite passivation layer at a single quantum well scale by hot pressing method solves the problems of solvent permeation and chemical degradation in the prior art, and significantly improves the efficiency and stability of perovskite solar cells.
Patent Information
- Application Number
- CN202411461731.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing two-dimensional perovskite passivation layer preparation methods have problems with solvent permeation and chemical degradation, resulting in limited efficiency and stability of perovskite solar cells.
The preparation temperature and pressure are controlled by the hot pressing method, so that the passivation molecules react with the three-dimensional perovskite to form a pure phase 2D perovskite passivation layer at a single quantum well scale.
The continuous phase change problem during the solution process is effectively avoided, and a perovskite film with adaptive energy levels is obtained, which improves the photoelectric conversion efficiency and stability of solar cells.
Smart Images

Figure CN119486542A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells and relates to a preparation method of a pure phase 2D perovskite passivation layer and an application thereof. Background Art
[0002] The two-dimensional (2D) perovskite passivation layer can inhibit ion migration, which improves the efficiency and stability of organic-inorganic metal hybrid perovskite solar cells. However, the two-dimensional perovskite with hybrid quantum wells will limit the generation and collection of carriers due to the higher exciton binding energy. At present, the more reactive passivation molecules will penetrate into the interior of the three-dimensional perovskite film through the solvent, thus forming a two-dimensional perovskite with mixed dimensions. In addition, the solvent used in the solution method will reconstruct the surface of the three-dimensional perovskite, causing chemical degradation of the three-dimensional perovskite film, which further hinders the improvement of the performance of perovskite solar cells. Summary of the invention
[0003] To improve the above problems, the present invention provides a method for preparing a pure phase 2D perovskite passivation layer, which directly reacts the passivation molecules with the three-dimensional perovskite by controlling the preparation temperature and the applied pressure through a hot pressing method to form a two-dimensional perovskite passivation layer of a single quantum well scale. The method of the present invention can not only effectively avoid the continuous phase change problem in the solution method process, but also obtain a perovskite film with a more suitable energy level. The solar cell including the perovskite film is more conducive to the transmission of charges, thereby effectively improving the photoelectric conversion efficiency and stability of the solar cell.
[0004] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0005] A method for preparing a pure phase 2D perovskite passivation layer comprises reacting passivation molecules directly on the surface of a perovskite absorption layer through a hot pressing method to generate a two-dimensional perovskite passivation layer with a single n value.
[0006] According to an embodiment of the present invention, the thickness of the passivation layer is 5-10 nm.
[0007] According to an embodiment of the present invention, the passivation layer is a phase-pure 2D perovskite passivation layer.
[0008] According to an embodiment of the present invention, the passivating molecule is selected from at least one of RP-type organic cation salts, phenylethylamine salts, butylammonium salts, octylammonium salts, diphenylethylammonium salts and 4-methoxyphenylethylammonium iodide. For example, the phenylethylamine salt, butylammonium salt, octylammonium salt and diphenylethylammonium salt can be iodide salts, bromide salts or chloride salts thereof. In the present invention, phenylethylamine, butylammonium, octylammonium and diphenylethylammonium are named as PEA, BA, OA and BPEA, respectively.
[0009] According to an embodiment of the present invention, the hot pressing method comprises modifying the passivation molecule solution on the substrate, and then applying pressure on the surface of the perovskite absorption layer by a hot pressing method. Preferably, the modification method can be a spin coating method. For example, the rotation speed of the spin coating is 1000 to 5000 rpm / s, exemplified by 1000, 2000, 3000, 4000 or 5000 rpm / s; the spin coating time is 1 to 60 s, exemplified by 1, 10, 20, 30, 40, 50 or 60 s.
[0010] According to an embodiment of the present invention, the passivation molecule solution is obtained by dissolving the passivation molecules in an alcohol solvent (such as isopropanol).
[0011] According to an embodiment of the present invention, the concentration of the passivation molecule solution is 1-10 mg / mL, exemplified by 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 mg / mL.
[0012] According to an embodiment of the present invention, the pressure of the hot pressing method is 20-200 MPa, exemplified by 20, 40, 60, 80, 100, 150 or 200 MPa; the heating temperature of the hot pressing method is 40-200°C, exemplified by 40, 80, 120, 160 or 200°C; the heating time of the hot pressing method is 1-10 min, exemplified by 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 min.
[0013] According to an embodiment of the present invention, the perovskite absorption layer is in the form of a thin film, preferably a three-dimensional perovskite thin film. Preferably, the thickness of the perovskite absorption layer is 200-900 nm.
[0014] The present invention also provides a perovskite film, which includes a perovskite absorption layer and the above-mentioned two-dimensional perovskite passivation layer with a single n value modified on the perovskite absorption layer.
[0015] The present invention also provides use of the above method and / or the above perovskite film in preparing a perovskite solar cell.
[0016] The present invention also provides a perovskite solar cell, which contains the above-mentioned perovskite film.
[0017] According to an embodiment of the present invention, the perovskite solar cell further comprises an electron transport layer. Preferably, the electron transport material used in the electron transport layer may be an n-type inorganic semiconductor or an n-type organic semiconductor. For example, the n-type inorganic semiconductor or n-type organic semiconductor includes but is not limited to: TiO 2 , mesoporous TiO 2 SnO 2 and one of ZnO-ZnS. Exemplarily, the electron transport layer is preferably SnO2 、TiO 2 / SnO 2 、ZnO-ZnS / mesoporous TiO 2 and TiO 2 / Mesoporous TiO 2 Preferably, the thickness of the electron transport layer is 10-120 nm.
[0018] For example, the electron transport layer can be prepared by spin coating, spray pyrolysis or chemical bath method on the electron transport material.
[0019] According to an embodiment of the present invention, the perovskite solar cell further comprises a hole transport layer. Preferably, the hole transport layer comprises a hole transport material and an additive. For example, the hole transport material is one of Spiro-OMeTAD, PTAA, P3HT or CuSCN; preferably Spiro-OMeTAD; the additive is tert-butylpyridine (tBP), Li salt (LiTFSI) or Co salt (FK209).
[0020] For example, the hole transport layer is prepared by spin coating or vacuum evaporation of a hole transport layer solution; for example, the hole transport layer solution contains a hole transport material and an additive.
[0021] According to an embodiment of the present invention, the perovskite solar cell further comprises a metal electrode. For example, the metal electrode is one of gold, silver, copper or aluminum; for another example, the thickness of the metal electrode is 30-200 nm. For example, the metal electrode is prepared by vacuum evaporation.
[0022] According to an embodiment of the present invention, the perovskite solar cell further comprises a transparent conductive substrate. Preferably, the transparent conductive substrate is one of ITO conductive glass and FTO conductive glass.
[0023] According to an embodiment of the present invention, the chemical formula of the perovskite material used in the perovskite film is A a M b X c , where A includes CH 3 NH 3 + HC(NH 2 ) 2 + , Cs + and Rb + At least one of; M is Pb 2+ Sn 2+ One of the following; X is I - Br - or I- Br - In total; a, b, c are the stoichiometric proportions of A, M, and X, respectively, a=1, b=1, c=3.
[0024] According to an embodiment of the present invention, the perovskite solar cell includes a transparent conductive substrate, an electron transport layer, the above-mentioned perovskite film, a hole transport layer and a metal electrode, which are arranged in sequence from top to bottom.
[0025] According to an embodiment of the present invention, the perovskite solar cell includes a transparent conductive substrate, a hole transport layer, the above-mentioned perovskite film, an electron transport layer and a metal electrode, which are arranged in sequence from top to bottom.
[0026] The present invention also provides a method for preparing the above-mentioned perovskite solar cell, which includes a method for preparing the above-mentioned pure phase 2D perovskite passivation layer.
[0027] According to an embodiment of the present invention, the preparation method further comprises pretreatment of the transparent conductive substrate, for example, cutting the transparent conductive substrate into fixed sizes and performing etching treatment, ultrasonically cleaning the prepared conductive substrates in a solvent, and performing ultraviolet ozone sterilization treatment after drying.
[0028] According to an embodiment of the present invention, the preparation method further comprises preparing an electron transport layer and / or a hole transport layer on the pretreated transparent conductive substrate.
[0029] According to an embodiment of the present invention, the preparation method further comprises subjecting the transparent conductive substrate coated with the electron transport layer and / or the hole transport layer to ultraviolet ozone sterilization treatment again, and transferring the conductive substrate to a glove box after the treatment.
[0030] According to an embodiment of the present invention, the preparation method further comprises preparing a perovskite absorption layer on the electron transport layer and / or the hole transport layer. For example, the preparation method of the perovskite absorption layer can be a spin coating method, a blade coating method, etc. Exemplarily, the perovskite precursor solution is applied to the electron transport layer by spin coating to form a perovskite absorption layer; the chemical formula of the perovskite absorption layer is A a M b X c , where A includes CH 3 NH 3 + HC(NH 2 ) 2 + , Cs + and Rb + At least one of; M is Pb 2+ Sn 2 + One of the following; X is I -Br - or I - Br - In total; a, b, c are the stoichiometric proportions of A, M, and X, respectively, a=1, b=1, c=3.
[0031] In one embodiment of the present invention, the method for preparing the perovskite precursor solution comprises: 2 or SnI 2 ), cationic iodides (FAI, MAI, RbI or CsI), lead bromide (PbBr 2 ), methylammonium chloride (MACl) and methylammonium bromide (MABr) are dissolved in an organic solvent and stirred; the organic solvent is one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), γ-butyrolactone (GBL) and 2-methoxyethanol (2-Me); the stirring temperature is 25-70°C, and the stirring time is 30-300min.
[0032] According to an embodiment of the present invention, the preparation method further comprises modifying a passivation molecule (e.g., 4-methoxyphenethylammonium iodide) on a substrate by a solution method, and then applying pressure to the surface of the perovskite absorption layer by a hot pressing method to obtain a perovskite film with a single n-value two-dimensional perovskite passivation. Preferably, the concentration of the passivation molecule solution used in the solution method is 1-10 mg / mL; the pressure of the hot pressing method is 20-200 MPa, the heating temperature of the hot pressing method is 40-200°C, and the heating time of the hot pressing method is 1-10 min.
[0033] According to an embodiment of the present invention, the preparation method further comprises preparing a hole transport layer and / or an electron transport layer on the perovskite film passivated by a single n-value two-dimensional perovskite.
[0034] According to an embodiment of the present invention, the preparation method further comprises preparing a metal electrode on the hole transport layer and / or the electron transport layer.
[0035] According to an embodiment of the present invention, the method for preparing the perovskite solar cell comprises the following steps:
[0036] (1) Cutting the transparent conductive substrate into fixed sizes and performing etching treatment (using a laser to scribe the P1 path of the module), ultrasonically cleaning the prepared conductive substrate in different solvents, and performing ultraviolet ozone sterilization treatment after drying;
[0037] (2) preparing an electron transport layer and / or a hole transport layer on the transparent conductive substrate treated in step (1);
[0038] (3) subjecting the transparent conductive substrate coated with the electron transport layer and / or the hole transport layer to UV-ozone sterilization treatment again, transferring the conductive substrate to a glove box after the treatment, and coating the perovskite precursor solution on the electron transport layer and / or the hole transport layer by spin coating to form a perovskite absorption layer;
[0039] (4) modifying 4-methoxyphenethylammonium iodide on a substrate by a solution method, and then applying pressure to the surface of the perovskite absorption layer by a hot pressing method to obtain a perovskite film with a single n-value two-dimensional perovskite passivation;
[0040] (5) preparing a hole transport layer and / or an electron transport layer on a perovskite film passivated by a single n-value two-dimensional perovskite;
[0041] (6) Depositing a metal electrode onto the hole transport layer and / or electron transport layer by vacuum evaporation (using laser to scribe the P3 path of the module).
[0042] Beneficial effects of the present invention:
[0043] (1) The method for preparing a two-dimensional perovskite passivation layer with a single n value provided by the present invention can, on the one hand, effectively passivate the defects on the surface and grain boundaries of the perovskite, reduce the non-compound radiation centers of the perovskite film, adjust the energy level of the solar cell, and thus improve the photoelectric conversion efficiency of the solar cell; on the other hand, the passivated perovskite film can inhibit ion migration, thereby effectively improving the stability of the solar cell.
[0044] (2) The perovskite film passivation method of the present invention is simple to operate, can be mass-produced, and can effectively avoid the disadvantages of the solvent method. The method of the present invention can also process large-area perovskite films, thereby providing a new strategy for the preparation of perovskite modules. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 X-ray diffraction patterns of the two-dimensional perovskite passivated perovskite film with a single n value prepared in Example 1 and the two-dimensional perovskite passivated perovskite film with mixed n values prepared in Comparative Example 1.
[0046] Figure 2 This is a steady-state fluorescence comparison diagram of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared in Example 1 and the perovskite film passivated by a two-dimensional perovskite with mixed n values prepared in Comparative Example 1.
[0047] Figure 3 This is a comparison chart of the photoelectric conversion efficiency of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared in Example 1 and the perovskite film passivated by a two-dimensional perovskite with mixed n values prepared in Comparative Example 1.
[0048] Figure 4This is a diagram of the photoelectric conversion efficiency of a two-dimensional perovskite passivated perovskite thin film solar module with a single n value prepared in Example 1.
[0049] Figure 5 This is a stability test comparison chart of the solar cell (module) of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared in Example 1 and the perovskite film passivated by a two-dimensional perovskite with mixed n values prepared in Comparative Example 1. DETAILED DESCRIPTION
[0050] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0051] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0052] Example 1
[0053] (1) FTO (fluorine-doped tin dioxide) conductive glass was cut into glass substrates of 15 mm x 15 mm in size. The cut glass substrates were ultrasonically cleaned in deionized water, acetone and ethanol for 15 min respectively, and then placed in a UV ozone machine for 15 min;
[0054] (2) SnO 2 The colloid (concentration of 15 wt %, purchased from Alfa Aesar) was diluted with water to 2.67 wt % and then spin-coated onto the treated FTO glass at a speed of 3000 rpm / s. After spin-coating for 30 s, it was annealed at 150 ° C in air atmosphere for 30 min.
[0055] (3) PbI 2 The molar ratio of FAPbI and FAI was 1.09:1, and they were dissolved in a mixed solvent of DMF and DMSO with a volume ratio of 8:1. The mixture was stirred continuously for 3 hours at room temperature to completely dissolve the mixture, thereby obtaining 1.4 M FAPbI. 3 Perovskite precursor solution; spin-coat the perovskite precursor solution onto FTO / SnO 2 The spin coating speed was 5000 rpm / s for 30 s, and the obtained intermediate phase film was heated at 100 °C for 60 minutes to generate a black perovskite phase FAPbI 3 film;
[0056] (4) Spin coat a 4 mg / mL 4-methoxyphenethyl ammonium iodide passivation molecule isopropanol solution on the blank FTO glass substrate treated in step (1) at a spin coating speed of 5000 rpm / s for 30 seconds. Then place it on the black perovskite phase FAPbI generated in step (3). 3 A pressure of 40 MPa was applied to the film and heated at 160 °C for 5 minutes. After the heating was completed, the glass slide with the 4-methoxyphenylethylammonium iodide passivation molecule was removed to obtain a black perovskite phase of FAPbI2 with a single n-value two-dimensional perovskite passivation. 3 film;
[0057] (5) Spin-coat the hole transport layer solution (72.3 mg Spiro-OMeTAD, 28.8 μL tBP 17.5 μL LiTFSI dissolved in 1 mL chlorobenzene) onto the perovskite phase FAPbI obtained in step (4) 3 On the film surface, the rotation speed was controlled at 4000 rpm / s and the spin coating time was 30 s;
[0058] (6) Finally, Au was deposited onto the hole transport layer by vacuum evaporation (the deposition thickness was 100 nm), and a specific mold was used to make the Au evaporation area 80 mm. 2 ;
[0059] Steps (3), (5) and (6) are all completed in a glove box.
[0060] Comparative Example 1
[0061] Compared with Example 1, the only difference is that: Step (4) prepares a mixed n-value two-dimensional perovskite passivated perovskite film by a solution method, and the specific method is: spin-coat a 4 mg / mL 4-methoxyphenethylammonium iodide passivation molecule isopropanol solution on the black perovskite phase FAPbI prepared in step (3) 3 The film surface was spin-coated at a speed of 5000 rpm for 30 s. After the spin coating was completed, the obtained film was heat-treated on a hot stage at an annealing temperature of 100° C. for 10 min.
[0062] Figure 1 The x-ray diffraction patterns of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared in Example 1 and the perovskite film passivated by a two-dimensional perovskite with mixed n values prepared in Comparative Example 1. It can be seen from the figure that the two-dimensional perovskite passivation layer prepared by the solution method is mixed-dimensional, while the two-dimensional perovskite passivation layer with a single n value prepared by the solid phase method of the present invention is single-dimensional, and the three-dimensional perovskite after passivation by the two-dimensional perovskite prepared by the solid phase method has better crystallinity than the solution method passivation.
[0063] Figure 2 The steady-state fluorescence comparison diagram of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared in Example 1 and the perovskite film passivated by a two-dimensional perovskite with mixed n values prepared in Comparative Example 1. It can be seen from the figure that the two-dimensional perovskite passivation layer prepared by the solution method is mixed-dimensional, while the two-dimensional perovskite passivation layer prepared by the solid phase method of the present invention is single-dimensional, and at the same time, the emission peak of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared by the solid phase method of the present invention at 800nm is much higher than that of the perovskite film passivated by the solution method, which shows that the two-dimensional perovskite passivation layer prepared by the solid phase method of the present invention has better passivation defect capability than the two-dimensional perovskite passivation layer prepared by the solution method.
[0064] Figure 3 The photoelectric conversion efficiency comparison diagram of the perovskite film passivated by a two-dimensional perovskite with a single n value prepared in Example 1 and the perovskite film passivated by a two-dimensional perovskite with mixed n values prepared in Comparative Example 1 is shown. It can be seen from the figure that the perovskite solar cell prepared by the two-dimensional perovskite passivation layer with a single n value prepared by the solid phase method of the present invention has a higher open circuit voltage and short circuit current than the cell prepared by the mixed n value; indicating that the perovskite film passivated by a two-dimensional perovskite with a single n value prepared by the solid phase method of the present invention has a better charge extraction capability.
[0065] Figure 4 This is a diagram of the photoelectric conversion efficiency of the perovskite thin film solar module passivated by a two-dimensional perovskite with a single n value prepared in Example 1. It can be seen from the figure that the black perovskite phase FAPbI 3 Thin-film perovskite solar cell module (14cm 2 ) has an open circuit voltage of 6.69 V and a current of 4.2 mA / cm 2 The short-circuit current is 80.07%, the fill factor is 80.07%, and its efficiency is 22.49%.
[0066] Figure 5 This is a stability test comparison diagram of the solar cell (module) of the perovskite film with a single n-value two-dimensional perovskite passivation prepared in Example 1 and the perovskite film with a mixed n-value two-dimensional perovskite passivation prepared in Comparative Example 1. It can be seen from the figure that the packaged perovskite module is subjected to a continuous light stability test under one sun, and the black perovskite phase FAPbI2O3 with a single n-value two-dimensional perovskite passivation prepared by the solid phase method of the present invention is 3 Thin-film perovskite module T 80 The T of the perovskite module of the two-dimensional perovskite passivated perovskite film with mixed n value prepared by solution method is 520h. 80 The solid phase method is used to prepare a black perovskite FAPbI2 with a single n-value two-dimensional perovskite passivation.3 The perovskite module of the thin film has better continuous light stability than the perovskite module of the perovskite film passivated by two-dimensional perovskite with mixed n values prepared by solution method.
[0067] Example 2
[0068] (1) FTO (fluorine-doped tin dioxide) conductive glass was cut into glass substrates of 15 mm x 15 mm in size. The cut glass substrates were ultrasonically cleaned in deionized water, acetone and ethanol for 15 min respectively, and then placed in a UV ozone machine for 15 min;
[0069] (2) Tetraisopropoxytitanium (purchased from Greatcell solar) was dissolved in water to obtain a 0.2 M tetraisopropoxytitanium aqueous solution, which was then spin-coated onto the washed FTO layer at a spin-coating speed of 3000 rpm / s for 30 s. 2 The substrate with the layer structure was annealed at 550° C. in an air atmosphere for 30 minutes, and after the temperature dropped to room temperature, the substrate was transferred to a glove box;
[0070] (3) PbI 2 The molar ratio of FAPbI and FAI was 1.09:1 and dissolved in a mixed solvent of DMF and DMSO (8:1). The mixture was stirred for 3 hours at room temperature to completely dissolve the mixture and obtain 1.4 M FAPbI. 3 Perovskite precursor solution; spin coating the perovskite precursor solution onto FTO / dense mesoporous TiO 2 The rotation speed was 5000 rpm / s for 30 s, and the obtained intermediate phase film was heated at 100 °C for 60 minutes to generate a black perovskite phase FAPbI 3 film;
[0071] (4) Spin coat a 4 mg / mL 4-methoxyphenethyl ammonium iodide passivation molecule isopropanol solution on the blank FTO glass substrate treated in step (1) at a spin coating speed of 5000 rpm / s for 30 seconds. Then place it on the black perovskite phase FAPbI generated in step (3). 3 A pressure of 40 MPa was applied to the film and heated at 160 °C for 5 minutes. After the heating was completed, the glass slide with the 4-methoxyphenylethylammonium iodide passivation molecule was removed to obtain a black perovskite phase of FAPbI2 with a single n-value two-dimensional perovskite passivation. 3 film;
[0072] (5) Spin-coat the hole transport layer solution (72.3 mg Spiro-OMeTAD, 28.8 μL tBP 17.5 μL LiTFSI dissolved in 1 mL chlorobenzene) onto the perovskite phase FAPbI obtained in step (4) 3 On the film surface, the rotation speed was controlled at 4000 rpm / s and the spin coating time was 30 s;
[0073] (6) Finally, Au was deposited onto the hole transport layer by vacuum evaporation (the deposition thickness was 100 nm), and a specific mold was used to make the Au evaporation area 80 mm. 2 ;
[0074] Steps (3), (5) and (6) are all completed in a glove box.
[0075] Example 3
[0076] (1) FTO (fluorine-doped tin dioxide) conductive glass was cut into glass substrates of 15 mm x 15 mm in size, and the cut glass substrates were ultrasonically cleaned in deionized water, acetone, and ethanol for 15 min, respectively, and then placed in a UV ozone machine for 15 min;
[0077] (2) SnO 2 The colloid (concentration of 15 wt %, purchased from Alfa Aesar) was diluted with water to 2.67 wt % and then spin-coated onto the treated FTO glass at a speed of 3000 rpm / s. After spin-coating for 30 s, it was annealed at 150 ° C in air atmosphere for 30 min.
[0078] (3) PbI 2 The molar ratio of FAPbI and FAI was 1.09:1, and they were dissolved in a mixed solvent of DMF and DMSO with a volume ratio of 8:1. The mixture was stirred continuously for 3 hours at room temperature to completely dissolve the mixture, thereby obtaining 1.4 M FAPbI 3 Perovskite precursor solution; apply the perovskite precursor solution to FTO / SnO 2 The distance between the scraper and the substrate was 100 μm, and the scraping speed was 8 mm / s. The obtained mesophase film was heated at 100 °C for 60 minutes to generate black perovskite phase FAPbI 3 film;
[0079] (4) Spin coat a 4 mg / mL 4-methoxyphenethyl ammonium iodide passivation molecule isopropanol solution on the blank FTO glass substrate treated in step (1) at a spin coating speed of 5000 rpm / s for 30 seconds. Then place it on the black perovskite phase FAPbI generated in step (3). 3A pressure of 40 MPa was applied to the film and heated at 160 °C for 5 minutes. After the heating was completed, the glass slide with the 4-methoxyphenylethylammonium iodide passivation molecule was removed to obtain a black perovskite phase of FAPbI2 with a single n-value two-dimensional perovskite passivation. 3 film;
[0080] (5) Spin-coat the hole transport layer solution (72.3 mg Spiro-OMeTAD, 28.8 μL tBP 17.5 μL LiTFSI dissolved in 1 mL chlorobenzene) onto the perovskite phase FAPbI obtained in step (4) 3 On the film surface, the rotation speed was controlled at 4000 rpm / s and the spin coating time was 30 s;
[0081] (6) Finally, Au was deposited onto the hole transport layer by vacuum evaporation (the deposition thickness was 100 nm), and a specific mold was used to make the Au evaporation area 80 mm. 2 ;
[0082] Steps (3), (5) and (6) are all completed in a glove box.
[0083] Example 4
[0084] (1) Cut FTO (fluorine-doped tin dioxide) conductive glass into glass substrates of 50 mm x 50 mm in size and etch them using laser (use green laser to scribe the P1 path of the module, where the power is 30% and the frequency is 200 kHz). The etched glass substrates are ultrasonically cleaned in deionized water, acetone and ethanol for 15 min respectively, and then placed in a UV ozone machine for 15 min;
[0085] (2) SnO 2 The colloid (concentration of 15 wt %, purchased from Alfa Aesar) was diluted with water to 2.67 wt % and then spin-coated onto the treated FTO glass at a speed of 3000 rpm / s. After spin-coating for 30 s, it was annealed at 150 ° C in air atmosphere for 30 min.
[0086] (3) PbI 2 The molar ratio of FAPbI and FAI was 1.09:1, and they were dissolved in a mixed solvent of DMF and DMSO with a volume ratio of 8:1. The mixture was stirred continuously for 3 hours at room temperature to completely dissolve the mixture, thereby obtaining 1.4 M FAPbI 3 Perovskite precursor solution; spin-coat the perovskite precursor solution onto FTO / SnO 2 The rotation speed was 5000 rpm / s for 30 s, and the obtained intermediate phase film was heated at 100 °C for 60 minutes to generate a black perovskite phase FAPbI 3 film;
[0087] (4) Spin coat a 4 mg / mL 4-methoxyphenethyl ammonium iodide passivation molecule isopropanol solution on the blank FTO glass substrate treated in step (1) at a spin coating speed of 5000 rpm / s for 30 seconds. Then place it on the black perovskite phase FAPbI generated in step (3). 3 A pressure of 40 MPa was applied to the film and heated at 160 °C for 5 minutes. After the heating was completed, the glass slide with the 4-methoxyphenylethylammonium iodide passivation molecule was removed to obtain a black perovskite phase of FAPbI2 with a single n-value two-dimensional perovskite passivation. 3 film;
[0088] (5) Spin-coat the hole transport layer solution (72.3 mg Spiro-OMeTAD, 28.8 μL tBP 17.5 μL LiTFSI dissolved in 1 mL chlorobenzene) onto the perovskite phase FAPbI obtained in step (4) 3 On the film surface, the spin coating speed was controlled to be 4000 rpm / s and the spin coating time was 30 s. The P2 track of the module was scribed with a laser, where the power was 25% and the frequency was 200 kHz.
[0089] (6) Finally, Au was deposited onto the hole transport layer by vacuum evaporation (the deposition thickness was 100 nm), and a specific mold was used to make the Au evaporation area 80 mm. 2 ; Use laser to scribe the P3 track of the module, where the power is 27.5% and the frequency is 200kHz;
[0090] Steps (3), (5) and (6) are all completed in a glove box.
[0091] Example 5
[0092] (1) FTO (fluorine-doped tin dioxide) conductive glass was cut into glass substrates of 15 mm x 15 mm in size, and the cut glass substrates were ultrasonically cleaned in deionized water, acetone, and ethanol for 15 min, respectively, and then placed in a UV ozone machine for 15 min;
[0093] (2) SnO 2 The colloid (concentration of 15 wt %, purchased from Alfa Aesar) was diluted with water to 2.67 wt % and then spin-coated onto the treated FTO glass at a speed of 3000 rpm / s. After spin-coating for 30 s, it was annealed at 150 ° C in air atmosphere for 30 min.
[0094] (3) PbI 2The molar ratio of MAPbI and MAI was 1.09:1, and the mixture was dissolved in a DMF and DMSO mixed solvent with a volume ratio of 8:1. The mixture was stirred continuously for 3 hours at room temperature to completely dissolve the mixture, thereby obtaining 1.4 M MAPbI. 3 Perovskite precursor solution; spin-coat the perovskite precursor solution onto FTO / SnO 2 The rotation speed was 5000 rpm / s for 30 s, and the obtained intermediate phase film was heated at 100 °C for 60 minutes to generate black perovskite phase MAPbI 3 film;
[0095] (4) 4 mg / mL of 4-methoxyphenethylammonium iodide passivation molecules were dissolved in isopropanol and spin-coated on the blank FTO glass substrate treated in step (1) at a spin-coating speed of 5000 rpm / s for 30 s. The substrate was then placed on the black perovskite phase MAPbI generated in step (3). 3 A pressure of 40 MPa was applied to the film and heated at 160 °C for 5 minutes. After heating, the glass slide with the 4-methoxyphenylethylammonium iodide passivation molecule was removed to obtain a black perovskite phase of MAPbI2 with a single n-value two-dimensional perovskite passivation. 3 film;
[0096] (5) Spin-coat the hole transport layer solution (72.3 mg Spiro-OMeTAD, 28.8 μL tBP 17.5 μL LiTFSI dissolved in 1 mL chlorobenzene) onto the MAPbI perovskite phase obtained in step (4). 3 On the film surface, the rotation speed was controlled at 4000 rpm / s and the spin coating time was 30 s;
[0097] (6) Finally, Au was deposited onto the hole transport layer by vacuum evaporation (the deposition thickness was 100 nm), and a specific mold was used to make the Au evaporation area 80 mm. 2 ;
[0098] Steps (3), (4), (5) and (6) are all completed in a glove box.
[0099] Example 6
[0100] The preparation steps and material selection of this embodiment are the same as those of Embodiment 1, except that the electron transport layer material in step (2) is TiO 2 / Mesoporous TiO 2 Layer (TiO 2 / Mesoporous TiO 2 The layer materials were purchased from Youxuan Technology Co., Ltd., and the remaining preparation steps and material selection were the same as in Example 1.
[0101] Example 7
[0102] The preparation steps and material selection of this embodiment are the same as those of Embodiment 1, except that in step (3), PbI 2 and FAI were dissolved in 2-ME (2-methoxyethanol) at a molar ratio of 1.09:1, and stirred continuously for 1 hour under heating conditions at 70°C to completely dissolve, thereby obtaining FAPbI with a concentration of 1.2 M. 3 The perovskite precursor solution, other preparation steps and material selection are the same as in Example 1.
[0103] Example 8
[0104] The preparation steps and material selection of this embodiment are the same as those of Embodiment 1, except that the hole transport layer material in step (5) is PTAA layer, and the hole transport layer solution (30 mg PTAA, 10 μL tBP, 5 μL LiTFSI dissolved in 1 mL chlorobenzene) is spin-coated onto the perovskite phase FAPbI obtained in step (4) by spin coating. 3 On the film surface, the rotation speed was controlled to be 2000 rpm / s and the spin coating time was 30 s; the remaining preparation steps and material selection were the same as in Example 1.
[0105] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a pure phase 2D perovskite passivation layer, characterized in that: The method includes reacting the passivation molecules directly on the surface of the perovskite absorption layer through a hot pressing method to generate a two-dimensional perovskite passivation layer with a single n value.
2. The method according to claim 1, characterized in that The passivation molecule is selected from at least one of RP-type organic cation salts, phenylethylamine salts, butylammonium salts, octylammonium salts, bisphenylethylammonium salts and 4-methoxyphenylethylammonium iodide.
3. The method according to claim 1, characterized in that The hot pressing method comprises modifying a passivation molecule solution on a substrate, and then applying pressure on the surface of the perovskite absorption layer by a hot pressing method. Preferably, the pressure of the hot pressing method is 20-200 MPa; the heating temperature of the hot pressing method is 40-200° C.; and the heating time of the hot pressing method is 1-10 min.
4. A perovskite film, characterized in that: The invention comprises a perovskite absorption layer and a two-dimensional perovskite passivation layer with a single n value prepared by the method described in any one of claims 1 to 3 and modified on the perovskite absorption layer.
5. Use of the method according to any one of claims 1 to 3 and / or the perovskite film according to claim 4 in preparing a perovskite solar cell.
6. A perovskite solar cell, characterized in that: It contains the perovskite thin film according to claim 4.
7. The battery according to claim 6, characterized in that The perovskite solar cell also includes an electron transport layer. Preferably, the electron transport material used in the electron transport layer may be an n-type inorganic semiconductor or an n-type organic semiconductor. For example, the n-type inorganic semiconductor or n-type organic semiconductor includes but is not limited to one of TiO2, mesoporous TiO2, SnO2 and ZnO-ZnS. Preferably, the thickness of the electron transport layer is 10-120 nm. Preferably, the perovskite solar cell further comprises a hole transport layer. Preferably, the hole transport layer comprises a hole transport material and an additive. For example, the hole transport material is one of Spiro-OMeTAD, PTAA, P3HT or CuSCN. Preferably, the perovskite solar cell further comprises a metal electrode, for example, the metal electrode is one of gold, silver, copper or aluminum. Preferably, the thickness of the metal electrode is 30-200 nm. Preferably, the perovskite solar cell further includes a transparent conductive substrate. Preferably, the chemical formula of the perovskite material used in the perovskite film is A a M b X c , where A includes CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + At least one of; M is Pb 2+ Sn 2+ One of the following; X is I - Br - or I - Br - In total; a, b, c are the stoichiometric proportions of A, M, and X, respectively, a=1, b=1, c=3.
8. The method for preparing a perovskite solar cell according to claim 6 or 7, characterized in that: The preparation method includes the preparation method of the pure phase 2D perovskite passivation layer according to any one of claims 1 to 3.
9. The preparation method according to claim 8, characterized in that: The preparation method further comprises preparing an electron transport layer and / or a hole transport layer on the pre-treated transparent conductive substrate. Preferably, the preparation method further comprises preparing a perovskite absorption layer on the electron transport layer and / or the hole transport layer. Preferably, the chemical formula of the perovskite absorption layer is A a M b X c , where A includes CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + At least one of; M is Pb 2+ Sn 2+ One of the following; X is I - Br - or I - Br - In total; a, b, c are the stoichiometric proportions of A, M, and X, respectively, a=1, b=1, c=3. Preferably, the preparation method further comprises modifying the passivation molecules on the substrate by a solution method, and then applying pressure to the surface of the perovskite absorption layer by a hot pressing method to obtain a perovskite film with a single n-value two-dimensional perovskite passivation. Preferably, the preparation method further comprises preparing a hole transport layer and / or an electron transport layer on the perovskite film passivated by a single n-value two-dimensional perovskite. Preferably, the preparation method further comprises preparing a metal electrode on the hole transport layer and / or the electron transport layer.
10. The preparation method according to claim 8 or 9, characterized in that: The steps include: (1) Cutting the transparent conductive substrate into fixed sizes and performing etching treatment (using a laser to scribe the P1 path of the module), ultrasonically cleaning the prepared conductive substrate in different solvents, and performing ultraviolet ozone sterilization treatment after drying; (2) Prepare an electron transport layer and / or a hole transport layer on the transparent conductive substrate processed in step (1); (3) Re-treat the transparent conductive substrate coated with the electron transport layer and / or the hole transport layer with ultraviolet ozone sterilization. After the treatment, transfer the conductive substrate to a glove box, and spin-coat the perovskite precursor solution onto the electron transport layer and / or the hole transport layer to form a perovskite absorption layer; (4) Modify 4-methoxyphenethylammonium iodide on the substrate by solution method, and then apply pressure on the surface of the perovskite absorption layer by the <8003220>240209-Z241963CPCN> hot pressing method to obtain a perovskite film passivated by single-n value two-dimensional perovskite; (5) Prepare a hole transport layer and / or an electron transport layer on the perovskite film passivated by single-n value two-dimensional perovskite; (6) Deposit a metal electrode on the hole transport layer and / or the electron transport layer by vacuum evaporation.
Citation Information
Patent Citations
Passivator for passivating perovskite thin film layer and application thereof
CN115498109A
Efficient and stable heterojunction perovskite solar cell module and preparation method thereof
CN116406176A
Application of compound in manufacturing perovskite thin-film solar cell and perovskite thin-film solar cell manufactured by using compound
CN117222237A
Hole transport layer of n-i-p type perovskite solar cell, perovskite solar cell and preparation method and application of perovskite solar cell
CN118401021A
Perovskite film passivation device
CN219499937U
Cited By
A perovskite using a co-crystal two-dimensional perovskite for surface passivation and a passivation method and application thereof
CN122784292A